2017
DOI: 10.1177/0018578717720310
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes Associated With Phenobarbital Use With or Without Benzodiazepines for Alcohol Withdrawal Syndrome: A Systematic Review

Abstract: Benzodiazepines are the drug of choice for alcohol withdrawal syndrome (AWS); however, phenobarbital is an alternative agent used with or without concomitant benzodiazepine therapy. In this systematic review, we evaluate patient outcomes with phenobarbital for AWS. Medline, Cochrane Library, and Scopus were searched from 1950 through February 2017 for controlled trials and observational studies using ["phenobarbital" or "barbiturate"] and ["alcohol withdrawal" or "delirium tremens."] Risk of bias was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Furthermore, overall safety profiles of barbiturates were comparable to those of BZDs across all studies included. Hammond et al, evaluated patient outcomes associated with phenobarbital use with or without BZDs for AWS by reviewing four controlled trials and five observational studies [ 18 ]. These authors concluded that phenobarbital may have a role in AWS treatment alongside BZDs or as monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overall safety profiles of barbiturates were comparable to those of BZDs across all studies included. Hammond et al, evaluated patient outcomes associated with phenobarbital use with or without BZDs for AWS by reviewing four controlled trials and five observational studies [ 18 ]. These authors concluded that phenobarbital may have a role in AWS treatment alongside BZDs or as monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are limited data on the use of fixed-dose phenobarbital for the management of AWS in surgical-trauma patients. 27,37 The prevalence of alcohol use in trauma patients has been reported to be as high as 50%. 4,38 However, AWS diagnosis in these patients is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital properties, including its long half-life and predictable kinetics, support the use of a fixed-dose regimen approach over a symptom-triggered approach, 23,28,33 especially because the principles of the symptom-triggered approach have not been validated with the use of phenobarbital. 27,37 The efficacy of the symptom-triggered approach relies on frequent assessment of patients’ symptoms using a validated scoring tool and careful attention to the overall condition of the patient by the evaluating clinician. 10 Because scoring tools such as CIWA-Ar and the MINDS rely on a constellation of autonomic signs and subjective symptoms, the presence of other acute illnesses specifically in the ICU might result in increased patients’ scores unrelated to AWS and improper use of the symptom-triggered approach for management of AWS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol (ethanol) is a central nervous system depressant, which triggers an adaptive process and the molecular changes associated with tolerance leading to imbalance of excitation and inhibition (Olsen and Spigelman, 2012). This molecular change in network leads to a wide range of complications, such as a neuroexcitatory effect, that plays an important role in AWS and may contribute to increased LOS and mortality (Connor et al, 2016;Hammond et al, 2017).…”
Section: Discussionmentioning
confidence: 99%